Lightness data extracted from core images of sediment core GeoB24007-1 - Thomas Westerhold (PANGAEA, 2024)
Field data: Lightness data extracted from core images of gravity corer sediments collected during project Kerguelen Plateau Sediment Drifts with RV Sonne Cruise SO272 in February and March 2020. Red, Green, Blue, Hue, Saturation, Lightness data were extracted from a 5 cm long and 0.2 mm wide area in the core center using the IGOR PRO software. The gravity cores were retrieved from the Labuan and Gaggatt Basin spanning Plio-Pleistocene to Eocene sediments. Lightness data were extracted to characterise the color of the sediment and document changes.